Human NK Cell Development: One Road or Many? - Cichocki, Frank; Grzywacz, Bartosz; Miller, Jeffrey S. (Frontiers in Immunology, 2019)
CD3-CD56+ NK cells develop from CD34+ hematopoietic progenitors (HPCs) in vivo, and this process can be recapitulated in vitro. The prevailing model is that human NK cell development occurs along a continuum whereby common lymphocyte progenitors (CLPs) gradually downregulate CD34 and upregulate CD56. Acquisition of CD94 marks commitment to the CD56bright stage, and CD56bright NK cells subsequently differentiate into CD56dim NK cells that upregulate CD16 and killer immunoglobulin-like receptors (KIR). Support for this linear model comes from analyses of cell populations in secondary lymphoid tissues and in vitro studies of NK cell development from HPCs. However, several lines of evidence challenge this linear model and suggest a more branched model whereby different precursor populations may independently develop into distinct subsets of mature NK cells. A more definitive understanding of human NK cell development is needed to inform in vitro differentiation strategies designed to generate NK cells for immunotherapy. In this review, we summarize current evidence supporting the linear and branched models of human NK cell development and the challenges associated with reaching definitive conclusions.